Narrating the future in Siberia : childhood, adolescence and autobiography among young Eveny - Ulturgasheva, Olga (Berghahn Books, 2012)
The wider cultural universe of contemporary Eveny is a specific and revealing subset of post-Soviet society. From an anthropological perspective, the author seeks to reveal not only the Eveny cultural universe but also the universe of the children and adolescents within this universe. The first full-length ethnographic study among the adolescence of Siberian Indigenous peoples, it presents the young people's narratives about their own future and shows how they form constructs of time, space, agency and personhood through the process of growing up and experiencing their social world. The study.